2022
DOI: 10.3390/app12105189
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Identified Genomic Regions Associated with Various Agronomic and Physiological Traits in Barley under Abiotic Stresses

Abstract: Climate change has caused breeders to focus on varieties that are able to grow under unfavorable conditions, such as drought, high and low temperatures, salinity, and other stressors. In recent decades, progress in biotechnology and its related tools has provided opportunities to dissect and decipher the genetic basis of tolerance to various stress conditions. One such approach is the identification of genomic regions that are linked with specific or multiple characteristics. Cereal crops have a key role in su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 180 publications
0
9
0
Order By: Relevance
“…Water availability is one of the most important parameters in determining global agricultural crop productivity [ 1 ]. Among abiotic stress, drought is known as one of the most important effects-reducing crop productivity worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Water availability is one of the most important parameters in determining global agricultural crop productivity [ 1 ]. Among abiotic stress, drought is known as one of the most important effects-reducing crop productivity worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The increased demand of barley for food, beer, and feed with concomitant reductions in yields perpetuated by climate change have accelerated research efforts towards understanding the genetic basis of drought associated agronomic traits and their responses in target environments. This approach enabled identification of QTL not only linked with yield, but also, physiological and biochemical responses to water deprivation [ 38 ]. Several abiotic stress tolerance mapping studies in barley have been reported [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…GWAS examines the entire genome to identify DNA variations related to the trait of interest [ 38 ]. GWAS has been successfully used in deciphering abiotic tolerance in rice [ 39 ], soybean [ 40 ], wheat [ 41 ], maize [ 42 ], sesame [ 43 ], barley [ 44 ], chickpea [ 45 ], rapeseed [ 46 ], cotton [ 47 , 48 , 49 ] and sorghum [ 50 , 51 ]. The primary goal of GWAS is to identify genomic areas linked with agronomic or morphological features or any phenotypes that can be markers, genes or quantitative trait loci (QTL) for gene discovery, introgressive hybridization and MAB [ 52 ] ( Table 1 ).…”
Section: Genomicsmentioning
confidence: 99%